Challenges of Using Information Technology in the Needs Analysis Design Process for Islamic Religious Education Learning - Diniati, Siti Wildan (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
In the 5.0 era, information technology has become an essential element of human life, particularly in education. With the availability of increasingly sophisticated information technology, education is rapidly evolving. The purpose of this study is to look into the usage of information technology in the needs analysis design process for Islamic religious education learning. The method employed is a qualitative approach with a case study method. This study was conducted at SDN Cengal 2 with Islamic religious education teachers as the sample. Data collection methods include observations, interviews, and documentation studies. The use of technology at SDN Cengal 2 in the learning needs analysis design process has been implemented, but there are several obstacles due to a lack of knowledge and skills in using various information technologies, as well as limited facilities and age issues. In terms of implementing information technology, laptops will be used to assist in determining Islamic religious education learning demands. In conclusion, the use of information technology can help in the process of analyzing learning needs. Still, schools must continue to make efforts to support the skills of teachers to face current challenges and to support the design of learning needs.